MULTIMEDIA IN PICTURE SERIES AS TEACHING STRATEGY IN ENCOURAGING ENGLISH LEARNING MOTIVATION TO BENGKALA ELEMENTARY STUDENTS - Ni Putu Dilia Dewi; Dadang Hermawan; Dian Rahmani Putri (Yavana Bhasha : Journal of English Language Education, 2022)
This research focuses on using the strategy of multimedia in picture series to encourage elementary students’ motivation in learning English. The motivation and excitement of students in learning English at the elementary school specifically at SD Inklusi still lack excitement. Find out how does multimedia work to increase the students' learning excitement in English lesson. This study uses a qualitative method. The data source will be conducted for the grade 5th in SD No.2 Inklusi Desa Bengkala Buleleng. Methods of data collection using direct observation and interviews. Direct observation can be used in two months to learn more about the process of teaching and learning English by using multimedia in picture series. The data analysis techniques proposed by Miles and Huberman include data reduction, data presentation, and conclusions or verification. There are three points in this research method. The first point is how data is collected, the second point is how data is analyzed, and the third is how data analysis is presented. The results of this study indicate that using multimedia by picture series can increase students' learning desire and motivation with excitement which is reflected in their active response in a class by raising their hands trying to speak and expressing their ideas and thoughts automatically.